Analisis Perbandingan Kerusakan Jalan pada Ruas Jalan Lingkar Bypass Krian Menggunakan Metode PCI (Pavement Condition Index) dan Metode SDI (Surface Distress Index) - Risgun Alham; Ibnu Sholichin; Aulia Dewi Fatikasari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The Krian Bypass Ring Road is an alternative road built to reduce congestion at the center of economic activity in the Krian community. The Krian Bypass Ring Road is divided into 2 parts, namely the West Krian Bypass Ring Road with a length of 4.20 KM and the East Krian Bypass Ring Road with a length of 3.54 KM. Road damage can be caused by several factors, including water, changes in temperature, air temperature, weather, unstable soil conditions, pavement construction materials, poor compaction processes on the subgrade layer, vehicle volume, and also vehicle loads that exceed capacity (Nur, 2023). Several types of road damage resulting from road pavement in general are cracking, deformation, hole damage, surface texture damage, pavement edge damage, utility excavation patches and patches. This research uses PCI and SDI methods. In the PCI method, the severity of pavement damage is a function of 3 main factors, namely: type of damage, severity of damage, number or density of damage. The SDI method is the latest method in accordance with the 2011 Directorate General of Highways regarding road condition survey guidelines. By carrying out this research, it is hoped that we will be able to determine the value of the conditions on the Krian Bypass road, and identify the types of road damage. Knowing the comparison of road condition values ​​from the results of analysis using the PCI (Pavement Condition Index) and SDI (Surface Distress Index) methods.